Overreaction pasar terhadap harga saham setelah pengumuman pemberlakuan pembatasan kegiatan masyarakat (PPKM) darurat (Studi Pada Perusahaan Indeks LQ-45 di Bursa Efek Indonesia) - Linda Rambu Kuba Yowi (Universitas Negeri Padang, 2022)
The Covid-19 pandemic has had a major impact on the Indonesian economy, including the Indonesian capital market, so that it can cause an overreaction for investors to invest because the Covid-19 pandemic is considered bad news for investors. This study aims to determine whether there is an overreaction to stock prices after the announcement of the emergency PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat) on July 1, 2021, which was carried out by the President of the Republic of Indonesia, Joko Widodo. This study takes 14 samples of manufacturing companies that are members of the LQ45 Index during the period February-July 2021. This test uses a one sample t test. The results of this test also show that the loser's portfolio does not outperform the winner's portfolio. Based on the tests that have been carried out, it can be concluded that there is no overreaction in manufacturing companies after the announcement of the emergency PPKM.